The Effect Of Assertive Training For Reducing Violence Behavior In Skizofrenia Patients: Literature Review - Anak Agung Ayu Ratih Satya Utami; Ibrahim, Masdum; Heni Purnama (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2021)
Aims : Violent behavior is one of the positive signs and symptoms that appear in schizophrenic patients. One of the actions that can be done on schizophrenic patients with violent behavior problems is by conducting assertive training. The purpose of this study was to analyze previous research on the effect of Asertive Training in Reducing Symptoms in Violent Behavior: Literature Review   Methdos : This study was a literature review. The journal obtained from two data based, namely Google Scholar and Pubmed. The keywords used in the data based on Google Scholar were combination between assertive training, assertive training, schizophrenia, and violent behavior. Meanwhile, the keywords used in the data based on Pubmed were assertive training, assertive skills, schizophenia, mental illness, violence behavior. The inclusion criteria were studies conducted on patient with schizophrenia, with assertive training interventions. Journal in bahasa Indonesia and English included, randomized control trial or quasi experimental studies, and free full text. Results The results were obtained as many as 676 journals based on a combination of keywords, then screened through titles, abstracts, and also inclusion criteria, only six journals were reviewed.   Conclusions : Based on the results showed that assertive training was able to reduce violent behavior in schizophrenic patients.